Dose‐dependent naloxone‐induced morphine withdrawal symptoms in opioid‐dependent males—a double‐blinded, randomized study. Issue 8 (20th March 2020) - Weisshaar, Stefan; Brandt, Laura; Litschauer, Brigitte; Sheik‐Rezaei, Safoura; Moser, Laura; Nirnberger, Günther; Kühberger, Elisabeth; Bauer, Ulrike; Firbas, Christa; Gouya, Ghazaleh; Wolzt, Michael; Fischer, Gabriele
Abstract : Aims: Oral opioid preparations combined with naloxone are intended to induce a transient acute withdrawal syndrome to avoid intravenous misuse. This trial aimed to establish an appropriate morphine–naloxone dose ratio for an abuse‐deterrent oral opioid formulation. Methods: In a randomized, double‐blinded, 2 × 2 cross‐over trial, 43 patients with opioid use disorder were challenged with intravenous morphine HCl Ph.Eur. (75 mg; [morphine mono]) or morphine HCl Ph.Eur. and naloxone HCl Ph.Eur. at ratios of 100:1 (75 mg: 0.75 mg; [morphine–naloxone 100:1]) or 200:1 (75 mg: 0.375 mg; [morphine–naloxone 200:1]). Acute naloxone‐induced opioid withdrawal was evaluated using subjective (Short Opiate Withdrawal Scale–German [SOWS‐G]) and observer‐rated (Objective Opiate Withdrawal Scale [OOWS], Wang scale) questionnaires, and physiological parameters. For statistical analysis, the area under the curve between baseline and 20 minutes after drug administration of the outcome variables was calculated. Results: Intravenous morphine–naloxone caused rapid withdrawal symptoms. Coadministration of naloxone dose‐dependently (morphine–naloxone 100:1 > morphine–naloxone 200:1) increased SOWS‐G, OOWS and Wang Scale area under the curve when compared to morphine mono, respectively (all P < .0001). A similar response was detectable for changes of pupil diameter. Blood pressure and respiratory rate changed heterogeneously, and heart rate was unaltered by morphine without or with naloxone. Conclusion: Morphine–naloxone 100:1 effectively suppresses the pleasurable effects of intravenous morphine and results in an aversive withdrawal reaction. A lower naloxone concentration as used in morphine–naloxone 200:1 does not appear to be appropriate to prevent intravenous morphine misuse.